THE RELATIONSHIP BETWEEN LANGUAGE AND CULTURE - Dinora Jabborova; Ramazonova Surayyo (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Language and culture exist in a continuous and dynamic relationship, shaping how individuals perceive the world and interact within it. This article narratively explores how language serves not only as a medium of communication but also as a repository of cultural knowledge, values, and traditions. By drawing on classical and contemporary linguistic theories, the study illustrates that language reflects cultural realities while simultaneously influencing thought and behavior.